Ang Pagbenta sa Imahen ng Kalalakihan sa mga Piling Tindahang Pandamit sa Pilipinas (Selling the Image of Masculinity Among Selected Philippine Clothing Stores) - Canete, Reuben Ramas (Plaridel Journal of Communication, Media, and Society; Vol 8 No 1 (2011): Regular Issue)
The concept of space as "neutral" has been critiqued in the contemporary period as a form of occlusion for other acts that are performed by its actors, the masses that populate this space is an active location occupied by social and individual agency, resulting in the "multifunctionality" of this space. In the present context, Filipino public space is defined by urbanization as determined by capitalistic economic forces that interlink labor bodies and consumerist products within a comprehensive system of material and sexual exchange. This paper looks at the phenomena of "selling" the image of masculinity among selected clothing and fashion stores like Bench, Folded & Hung, and Penshoppe as a manifestation of the functionalization of consumer space as a potential location for the male body to become a product itself in the new market of globalization, the shopping mall. Utilizing critical theory and political economy, the study analyzes the relations between material existence in the city during the age of globalization; the role that labor plays as both consumer and product; and the role that desire plays as an active mechanism in the development of the visual and sexual economy in the late period of capitalism. Another aim of this paper is to outline a theory of consumption that can be interrelated to Marx's theory of production, in order to produce a more comprehensive analysis of the effects of material existence in society, and in the lives of its people. Keywords: space, masculinity, theory of consumption, critical theory, political economy